Title In English; The Reality Of Translating Literary And Critical Terminology In The Era Of Globalization And Artificial Intelligence. - Malaoui Mahfoud; Korbaa Ali (جامعة الوادي - University of Eloued, 2025)
Abstract: This paper seeks to examine the state of critical terminology translation, both theoretical and applied, as a vital intermediary among scholars in the literary field, particularly in the context of globalization and artificial intelligence. It is our contention that the lack of terminological consistency and the absence of a unified translation framework among critics and linguistic academies in the Arab world have impeded the anticipated progress. A genuine process of intercultural exchange necessitates a forward-looking and well-informed vision that integrates the original translated term with the translator’s interpretative framework. This approach must align with the development of computational programs and the utilization of advanced technologies capable of processing and analyzing these linguistic variables, identifying emerging patterns through artificial intelligence, and applying acquired knowledge in real time.
Article .Journal of Arabic Language Sciences and Literature Vol. 17. N. 02
Keywords: critical term; translation; acculturation; globalization; artificial intelligence